2021
DOI: 10.1093/nar/gkab1160
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 RNA polymerase is a viral RNA capping enzyme

Abstract: SARS-CoV-2 is a positive-sense RNA virus responsible for the Coronavirus Disease 2019 (COVID-19) pandemic, which continues to cause significant morbidity, mortality and economic strain. SARS-CoV-2 can cause severe respiratory disease and death in humans, highlighting the need for effective antiviral therapies. The RNA synthesis machinery of SARS-CoV-2 is an ideal drug target and consists of non-structural protein 12 (nsp12), which is directly responsible for RNA synthesis, and numerous co-factors involved in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Increasing the NTP pool to 500 μM, the reaction would incorporate non-Watson–Crick base pairs and efficiently move on to the full-length product. Further, the authors in this study [ 18 ] found an IC 50 of 6.56 μM in their in vitro study, similar to our determination of 7.81 μM in the presence of 1 μM NTPs ( Figure 2 A). They also discuss several reasons why their value is much higher than the originally reported 0.77 μM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increasing the NTP pool to 500 μM, the reaction would incorporate non-Watson–Crick base pairs and efficiently move on to the full-length product. Further, the authors in this study [ 18 ] found an IC 50 of 6.56 μM in their in vitro study, similar to our determination of 7.81 μM in the presence of 1 μM NTPs ( Figure 2 A). They also discuss several reasons why their value is much higher than the originally reported 0.77 μM.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, a study demonstrated that the SARS-CoV-2 RdRp complex possesses GTPase activity and also indicated that GS-443902 can inhibit this reaction [ 18 ]. While the polymerase reaction without an inhibitor was carried out at a 500 μM NTP concentration, the NTP concentration was reduced to 1 μM for reactions containing the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In CoVs, the nsp13, nsp14 and nsp16 proteins have RTPase 25 , N 7-MTase 6 and 2′- O -MTase 7 activities, respectively. Thus, it was presupposed that the CoV capping mechanism occurs in a similar manner to the eukaryotic capping pathway, with the NiRAN domain functioning as the GTase 3 , 5 , 26 . However, evidence to support this claim is lacking.…”
Section: Mainmentioning
confidence: 99%
“…
The SARS-CoV-2 RNA genome contains a 5′-cap that facilitates translation of viral proteins, protection from exonucleases and evasion of the host immune response [1][2][3][4] . How this cap is made is not completely understood.
…”
mentioning
confidence: 99%
“…More than 95% identical to SARS-CoV counterpart, nsp12 of SARS-CoV-2 exhibits a similar sensitivity to the inhibitory effect of remdesivir, and the decreased enzymatic activity and thermostability ( Peng et al, 2020 ). Besides RdRP activity, SARS-CoV-2 nsp12 is responsible for viral RNA capping as a GTPase, adding a GTP nucleotide to the 5’ end of viral RNA via a 5’–5’ triphosphate linkage ( Walker et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%